Effect of core stability exercises on upper limb reaching in children with spastic hemiparetic cerebral palsy: a randomized controlled trial - Nadia Hassan Abd-Elhameed; Heballah Mohammed Kamal; Mai Elsayed Abbass (Bulletin of Faculty of Physical Therapy)
Abstract Background The core stability program is commonly utilized as an intervention method to improve postural control. This study aimed to evaluate the effect of core stability exercises on upper limb reaching in children with hemiparetic cerebral palsy (CP). For this purpose, 30 hemiparetic CP children of both sexes were recruited for the study. The children were between the ages of 4 and 6. According to the modified Ashworth scale (MAS), the degree of spasticity varied from 1 to 1 + , and for children who were selected, the average Trunk Control Measurement Scale (TCMS) ranged from 25 to 42. Children were assigned into two groups at random (study group and control group). The pediatric reach test (PRT) was used to assess each child both before and after two consecutive months of therapy. The children in both groups received the same program of selected physical therapy exercises, but the children in the study group also performed the selected physical therapy program in addition to the core stability exercises. Results By comparing the mean values of all assessed variables before and after therapy, both groups improved significantly (p = 0.0001). When comparing post-treatment outcomes, there were significant differences between the control and study groups in all assessed variables (p = 0.0001) in favor of the study group. Conclusion Core stability exercises may be used to improve reaching in children with hemiparetic cerebral palsy. Trial registration This study was authorized by the Faculty of Physical Therapy’s ethics committee under the number “REC/012/003125” and registered in ClinicalTrial.gov with the number “NCT05316090” on 9 April 2022 retrospectively.